Atvirosios ir uždarosios nekirčiuotos galūnės bei žodžių pradžios balsių trukmė bendrinėje lietuvių kalboje - Kaukėnienė, Lidija (Kalbotyra, 2005)
In this research, using instrumental and statistical methods, the vowel quantity at the end and at the beginning of the word was investigated. The results of the investigation showed that the short vowels of the open endings were 1.25 times longer than the vowels of the closed endings. Meanwhile the long vowels of the open endings were only 1.06 times longer than the vowels of the closed endings. Long and short vowels of the open beginnings were 1.3 times longer than the vowels of the closed beginnings.